Optimasi Pengelolaan Marketplace Usaha Rumahan di Imogiri - Ulfah Hidayati; Voettie Wisataone (Civitas Consecratio: Journal of Community Service and Empowerment, 2022)
The purpose of this Community Service (PkM) activity is to optimize marketplace management skills for home-based business actors. The purpose of home-based entrepreneurs here is housewives who are members of the PKK group in Imogiri sub-district, Bantul, and have a business that is run from home. In 2021, the UNY PkM Team consisting of lecturers and students has conducted training for the creation of a shopee marketplace and product photography. Furthermore, in 2022 the PkM Team conducted further training with the theme of optimizing marketplace management. In the training, pre-event and post-event assistance was carried out in addition to the two main materials presented. The training was attended by 30 participants who are members of the Imogiri Village PKK. Prior to the event, the PkM Team provided assistance to create product logos for business actors who did not yet have a logo. In this assistance, several business actors succeeded in creating logos for their products. Furthermore, the main material presented the topic of optimizing the management of the marketplace through SEO (Search Engine Optimization) and tips on building an online store brand. After delivering the main material, the PkM Team provided assistance to the participants to create keywords to optimize SEO. Some participants managed to get a lot of new keywords and some only got a few keywords for their online products due to limited training time. In this training, the UNY PkM Team provided a questionnaire to measure participants' understanding and participants' responses to the training event. From the questionnaire, it appears that the knowledge of the participants has increased and the participants have responded positively to the training provided.